Finanzas y filantropía en el Perú del siglo XIX El caso de José Sevilla Escajadillo: 1813-1886 - Reyes Flores, Alejandro (2006)
In the early 19 century Peruvians had the opportunity «to make money» in the same way as the thousands of foreigners who arrived in our country for that purpose. Those men followed two different paths to achieve fortune and a new social status in 19 th th century Peru: the opportunistic and mercenary use of the State mechanisms, and the «modern» implementation of responsible and creative work, savings, investment, reinvestment, education, compliance of law, giving value to time, living frugally and other modern ideas. Don José Sevilla follows the latter school of thought in this generation of 19 century Peruvians. In the first part of this essay we try to present how José Sevilla made his fortune. In the second one we describe and analyse the contents of his will and his philanthropic legacy to public institutions, relatives, friends in the United States and in 19 th century Peru. We shall previously reconstruct Peru and the northern coast as the general framework of the lengthy life on don José Sevilla, the origin of his wealth, the methodology of his work in the world of finances and his philanthropic legacy.